1998
DOI: 10.1002/hep.510270626
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of sinusoidal endothelial cells is a critical mechanism of preservation injury in rat liver transplantation

Abstract: In livers excised for transplantation, sinusoidal endothelium appears especially vulnerable to injury during organ preservation in the cold and subsequent reperfusion. The degree of endothelial cell injury correlates with functional impairment of the graft following transplantation. The mechanism of injury remains obscure, but endothelial cell damage has been described as coagulative necrosis secondary to irreversible physico-chemical damage. We investigated whether endothelial cell death is caused by apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
209
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 304 publications
(232 citation statements)
references
References 66 publications
17
209
0
6
Order By: Relevance
“…39 The extent of apoptosis after 1 hour of reperfusion was directly related to the duration of cold preservation, indicating that key events leading to apoptosis occur in the cold. A practical consequence of these studies is that there are now new rationales for the prevention of cold preservation injury based on proven events that occur in the cold.…”
Section: Discussionmentioning
confidence: 97%
“…39 The extent of apoptosis after 1 hour of reperfusion was directly related to the duration of cold preservation, indicating that key events leading to apoptosis occur in the cold. A practical consequence of these studies is that there are now new rationales for the prevention of cold preservation injury based on proven events that occur in the cold.…”
Section: Discussionmentioning
confidence: 97%
“…45,46 Kupffer cells also can contribute to IR injury through their ability to produce cytokines and reactive oxygen species (ROS) which contributes to SEC apoptosis. 47,48 A confounding factor in the IR injury response is the existence of hepatic zonation. A recent study demonstrated that SEC apoptosis was significantly enhanced in the presence of Kupffer cells, and that this was blocked by inhibition of ROS and inhibitors of caspase 3 and caspase 9, suggesting that Kupffer cell-derived ROS contributes to SEC apoptosis.…”
Section: Ischemia and Reperfusion Injurymentioning
confidence: 99%
“…Detection of apoptosis with the TUNEL-assay was performed as previously described by Gao et al 22 Briefly, 4, 12, and 24 h after 1 min of exposure to hypotonic stress cells were fixed in freshly prepared 4% paraformaldehyde in PBS (pH 7.2) for 30 min. The cells were treated with terminal deoxynucleotidyl transferase from calf thymus (Kit Boehringer) in the presence of fluorescein-dUTP and d-NTP.…”
Section: Tunel Assaymentioning
confidence: 99%